2018
DOI: 10.3390/ijgi7030115
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Transformation of Equality – Generalized Travelling Salesman Problem to Travelling Salesman Problem

Abstract: Abstract:The Equality-Generalized Travelling Salesman Problem (E-GTSP), which is an extension of the Travelling Salesman Problem (TSP), is stated as follows: given groups of points within a city, like banks, supermarkets, etc., find a minimum cost Hamiltonian cycle that visits each group exactly once. It can model many real-life combinatorial optimization scenarios more efficiently than TSP. This study presents five spatially driven search-algorithms for possible transformation of E-GTSP to TSP by considering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…By one means or the other (or even together), the best route is eventually provided. Aziz Ouaarab [13] and Zia et al [14] showed the different approaches to solve the TSP in specific cases, such as railway track optimization, robot movement, vehicle routing, among others. Wasser et al [15], in turn, successfully applied heuristic of trajectory planning in additive manufacturing of polymers.…”
Section: Starting Position Definition and Node Connections To Define ...mentioning
confidence: 99%
“…By one means or the other (or even together), the best route is eventually provided. Aziz Ouaarab [13] and Zia et al [14] showed the different approaches to solve the TSP in specific cases, such as railway track optimization, robot movement, vehicle routing, among others. Wasser et al [15], in turn, successfully applied heuristic of trajectory planning in additive manufacturing of polymers.…”
Section: Starting Position Definition and Node Connections To Define ...mentioning
confidence: 99%
“…Ben-Arieh et al . (2003) and Zia et al (2018) discuss "non-exact" transformations from the GTSP to TSP that provide heuristic solutions for the GTSP using existing algorithms for the TSP.…”
Section: Transformation To the Tspmentioning
confidence: 99%
“…These problems are solved transport and logistics management by the traveling salesman problem (TSP). Patrol route analysis in the area is arranged by the efficiency distance, time and cost of patrol operation planning (Zia et al 2018;Almahasneh & Koczy 2020). Therefore, these problems are interested in finding first solutions to solve these complications and to improve the efficiency of prevention and suppression patrol routes.…”
Section: Introductionmentioning
confidence: 99%